Acetaldehyde released by Lactobacillus plantarum enhances accumulation of pyranoanthocyanins in wine during malolactic fermentation. (June 2018) - Wang, Shaoyang; Li, Siyu; Zhao, Hongfei; Gu, Pan; Chen, Yuqi; Zhang, Bolin; Zhu, Baoqing
Abstract: This study investigated the evolution of acetaldehyde and pyranoanthocyanins in wine during malolactic fermentation, and further evaluated the correlation between acetaldehyde and pyranoanthocyanins. Cabernet Gernischt wine after alcoholic fermentation was inoculated with four lactic acid bacteria strains. Malolactic fermentation kinetics and wine characteristics were compared. Results showed these strains exhibited different kinetics on wine malolactic fermentation. Wine with Lactobacillus plantarum had lower reducing sugar, total acid, and yellowness. Lactobacillus plantarum elevated the level of acetaldehyde in wine model medium and wine during malolactic fermentation. Malolactic fermentation using Lactobacillus plantarum significantly increased the concentration of pyranoanthocyanins, whereas O. oeni strain reduced the level of pyranoanthocyanins in wine. Polymerized anthocyanins percentage in wine was significantly enhanced after fermentation with Lactobacillus plantarum . Principal component analysis indicated that the characteristics of these strains inoculated wines after malolactic fermentation were segregated. The findings from this study could provide useful information on the wine color improvement through malolactic fermentation with suitable lactic acid bacteria strains. Graphical abstract: Unlabelled Image Highlights: L. plantarum strains were capable to complete malolactic fermentation of wine. Acetaldehyde was accumulated during malolactic fermentation by L. plantarum . Pyranoanthocyanin level increased after malolactic fermentation by L. plantarum . Polymerized anthocyanins increased after malolactic fermentation by L. plantarum . Wine L* and a* were reduced after malolactic fermentation by L. plantarum .